2014
DOI: 10.1155/2014/504376
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Alexithymia, Anxiety, Depression, and Internet Addiction Severity in a Sample of Italian High School Students

Abstract: We aimed to assess whether Internet addiction (IA) severity was related to alexithymia scores among high school students, taking into account the role of gender differences and the possible effect of anxiety, depression, and age. Participants in the study were 600 students (ages ranging from 13 to 22; 48.16% girls) recruited from three high schools in two cities from Southern Italy. Participants completed a sociodemographic questionnaire, the Toronto Alexithymia Scale, the Internet Addiction Test, the Hamilton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
65
4
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 50 publications
(63 reference statements)
16
65
4
4
Order By: Relevance
“…These rates were higher than those found by most other studies. For example, alexithymia was 3.6% among Turkish medical students, 8.7% among UK nursing students, 16.7% among Italian high school students, and 17.92% among British undergraduate students . However, few other studies found slightly higher rates of alexithymia than those found in this study, such as Lala et al., who found it to be 26.1% of their undergraduate students.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…These rates were higher than those found by most other studies. For example, alexithymia was 3.6% among Turkish medical students, 8.7% among UK nursing students, 16.7% among Italian high school students, and 17.92% among British undergraduate students . However, few other studies found slightly higher rates of alexithymia than those found in this study, such as Lala et al., who found it to be 26.1% of their undergraduate students.…”
Section: Discussioncontrasting
confidence: 66%
“…Contrary to the results of most studies on alexithymia, levels of alexithymia in this study was significantly higher in female students (57.24 for females and 54.53 for males, t = 2.91, P ≤ 0.05). In most similar studies, higher levels of alexithymia were found among males . However, Mason et al .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…On the other hand, the relation between attention deficit and Internet addiction is stronger in the female group (Yen, Yen, Chen, Tang, & Ko, 2009). No gender differences were found in the (Scimeca et al, 2014). The results of another study (Kaess et al, 2014) showed that gender is a significant predictor of Pathological Internet Use.…”
Section: Introductionmentioning
confidence: 94%